2022
DOI: 10.1101/2022.07.21.501023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning from pre-pandemic data to forecast viral escape

Abstract: From early detection of variants of concern to vaccine and therapeutic design, pandemic preparedness depends on identifying viral mutations that escape the response of the host immune system. While experimental scans are useful for quantifying escape potential, they remain laborious and impractical for exploring the combinatorial space of mutations. Here we introduce a biologically grounded model to quantify the viral escape potential of mutations at scale. Our method - EVEscape - brings together fitness predi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 109 publications
2
36
0
Order By: Relevance
“…Therefore, a variety of computational approaches have been developed that attempt to predict escape by new viral variants. These approaches include basic transformations of deep mutational scanning data (Greaney, Starr and Bloom 2022), models that integrate antigenic data with phylogenetic (Neher et al 2016) or sequence data (Sun et al 2013;Harvey et al 2016), and neural networks that can be trained using deep mutational scanning data (Taft et al 2022) or sequence data alone (Hie et al 2021;Thadani et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a variety of computational approaches have been developed that attempt to predict escape by new viral variants. These approaches include basic transformations of deep mutational scanning data (Greaney, Starr and Bloom 2022), models that integrate antigenic data with phylogenetic (Neher et al 2016) or sequence data (Sun et al 2013;Harvey et al 2016), and neural networks that can be trained using deep mutational scanning data (Taft et al 2022) or sequence data alone (Hie et al 2021;Thadani et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Starr et al used deep mutational scanning to systematically address RBD mutation effects on protein expression, ACE2 interaction, and antibody recognition [12,13]. Recently, a structural investigation found that RBD-ACE2 binding affinity of the Omicron variant is similar to the Delta variant, and that Omicron spike displays significant antibody evasion [14], in line with earlier studies [1,2,15,16]. Ovchinnikov & Karplus used a kinetic model of B-cell affinity maturation to determine the importance of bivalent versus monovalent antibody-antigen interactions in vaccination and infection [17].…”
Section: Introductionmentioning
confidence: 63%
“…Currently, unsupervised methods trained on natural sequences have been surprisingly successful at learning from evolutionary sequences to predict variant effects. 5,6,[8][9][10][11][12][13][14][15] . Yet, these are often tasks involving single mutations or at single mutational depths.…”
Section: Introductionmentioning
confidence: 99%